2002
DOI: 10.1002/art.10083
|View full text |Cite
|
Sign up to set email alerts
|

COBRA combination therapy in patients with early rheumatoid arthritis: Long‐term structural benefits of a brief intervention

Abstract: Objective. The Combinatietherapie Bij Reumatoide Artritis (COBRA) trial demonstrated that stepdown combination therapy with prednisolone, methotrexate, and sulfasalazine (SSZ) was superior to SSZ monotherapy for suppressing disease activity and radiologic progression of rheumatoid arthritis (RA). The current study was conducted to investigate whether the benefits of COBRA therapy were sustained over time, and to determine which baseline factors could predict outcome.Methods. All patients had participated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
284
3
21

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 544 publications
(319 citation statements)
references
References 24 publications
11
284
3
21
Order By: Relevance
“…Another strategy of the rheumatologist for enhancing the efficacy of the combination of MTX plus SSZ is the addition of a third drug (e.g., hydroxychloroquine [13] or prednisone [14]) to the MTX-SSZ combination. Although the objective of this study was not to elucidate a mechanistic basis for the efficacy of the triple DMARD therapy, recent studies by our group (47) did indicate that CEM/SSZ cells displayed enhanced sensitivity to both chloroquine and dexamethasone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another strategy of the rheumatologist for enhancing the efficacy of the combination of MTX plus SSZ is the addition of a third drug (e.g., hydroxychloroquine [13] or prednisone [14]) to the MTX-SSZ combination. Although the objective of this study was not to elucidate a mechanistic basis for the efficacy of the triple DMARD therapy, recent studies by our group (47) did indicate that CEM/SSZ cells displayed enhanced sensitivity to both chloroquine and dexamethasone.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, addition of a third component such as hydroxychloroquine (12,13) or prednisone (14) is usually required to significantly improve clinical efficacy. Furthermore, one notable adverse effect observed was a persistent increase in plasma homocysteine levels in patients with RA who were receiving the combination of MTX and SSZ, compared with those receiving single-drug therapy (15,16).…”
mentioning
confidence: 99%
“…While no single agent was proven to be enough to control disease progression, current acceptable therapy for rheumatoid arthritis is aimed to attenuate disease activity with a combination of disease-modifying anti-rheumatic drugs such as methotrexate, sulfasalazine, leflunomide, hydroxychloroquine, cyclosporin, azathioprine, etc. (34)(35)(36). The purpose of a combination therapy is to obtain synergistically therapeutic effects of drugs with different immunomodulatory mechanisms and, in the meantime, to reduce side effects from each drug by decreasing their dosages.…”
Section: Herbs Used In Autoimmune Diseasementioning
confidence: 99%
“…Two European studies, COBRA (Combination Therapy in Rheumatoid Arthritis) and BeSt (Behandel-Stratieën) trial, found that a high-dose oral prednisone regimen (60 mg, tapering to 7.5 mg by week 6, then stopping after week 12) in combination with other conventional DMARDs substantially inhibited the progression of radiographic joint damage, and this effect was sustained over many years. 35,69 In particular, the BeSt study findings suggest that the addition of highdose prednisone therapy may mitigate the advantage of initial biologic therapy, in this case with infliximab, further supporting our approach of not using a biologic agent initially. To date, no studies have evaluated a more intermediate starting dose (ie, 20 mg/d).…”
Section: Treatment Approach Initial Treatment Approachmentioning
confidence: 71%